Paradigm Shift in Geriatric Low Back Pain Management: Integrating Influences, Experiences, and Consequences. Issue 5 (16th April 2018) - Simon, Corey B; Hicks, Gregory E
Abstract: Geriatric low back pain (LBP) can have a profound impact on physical activity and can cause a decline in physical function, which is a major health risk for older adults. Within the last decade, physical therapist management of LBP has shifted from an emphasis on pathoanatomical mechanisms, such as spine degeneration, to addressing psychological distress factors. Although this approach is promising, the complexity of LBP in older adults (including biological, psychological, cognitive, and social influences), which may differ from that in younger adults, must be considered. Further, outcome assessment should represent not only the LBP experience (eg, pain intensity, pain with movement) but also LBP consequences, such as physical activity decline and physical function decline. This perspective discusses influences on geriatric LBP, experiences, and consequences with the goal of facilitating standardized and comprehensive physical therapist management.